Pengaruh Return On Assets dan Debt To Equity Terhadap Return Saham Degan Inflasi Sebagai Pemoderasi - Umi Rahma Dhany; Ahmad Iskandar Rahmansyah (Politeknik Ganesha Medan, 2022)
Financial performance is one of the easiest ways to choose stock investments in a company. This is done so that the goal of investors to get the desired profit in the form of stock returns can be realized. Several previous studies were inconsistent in revealing the effect of financial performance on stock returns. So the purpose of this study is to determine the effect of financial performance with stock returns, which is then added to inflation as a moderating variable of the relationship. The independent variable consists of return on assets and debt to equity ratio, while the dependent variable is stock return. The population of this research is 30 Sharia stock issuers who are members of the Jakarta Islamic Index during the COVID-19 pandemic, namely 2020-2021. The sample of this research is 24 syariha stock issuers who are members of the Jakarta Islamic Index for 2 periods, namely 2020-2021. Data in the form of financial statements obtained from the IDX official website, then analyzed using the SMARTPLS 3 application for validity testing, reliability testing, analyzing the coefficient of determination, and hypothesis testing. The results showed that return on assets had no significant effect on stock returns. Likewise, the debt to equity ratio does not show any significant effect on stock returns. Furthermore, it is known that inflation is not a moderating variable of the effect of return on assets and debt to equity on stock returns.